Diarrhea risks by exposure to livestock waste in Vietnam using quantitative microbial risk assessment - Thu Le-Thi; Phuc Pham Duc; Zurbrugg, C.; Toan Luu-Quoc; Huong Nguyen-Mai; Tu Vu-Van; Hung Nguyen-Viet (Springer, 2017)
Objectives The aim of this paper was to assess the diarrhea risks caused by various pathogens among those exposed to biogas wastewater through different activities. Methods Application of quantitative microbial risk assessment (QMRA) of biogas wastewater was conducted in Hanam Province, Vietnam. A total of 451 representatives from households that use biogas were interviewed about their practices of handling biogas plant and reuse of biogas effluent for irrigation. In addition, 150 samples of biogas wastewater were analyzed for Escherichia coli, Cryptosporidium parvum, and Giardia lamblia. Risk characterization was calculated using Monte Carlo simulation. Results The annual diarrhea risk caused by exposure to biogas effluent through irrigation activities ranged from 17.4 to 21.1% (E. coli O157:H7), 1.0 to 2.3% (G. lamblia), and 0.2 to 0.5% (C. parvum), while those caused through unblocking drains connected to biogas effluent tanks were 22.0% (E. coli), 0.7% (G. lamblia), and 0.5% (C. parvum). Conclusions Further measures are needed to reduce the risk by either improving the microbial quality of biogas effluent or by ensuring the use of personal protective measures when exposed to biogas wastewater.